Trait-based approaches in arbuscular mycorrhizal fungi need to distinguish between response and effect traits - Urcelay, Roberto Carlos (2022)
Mycologists usually borrow models or theoretical frameworks from other ecological disciplines to test them in fungal ecology. For example, using models from plant and animal ecology, some attempts intended to classify fungi according to life-history strategies, or functional groups and guilds. In this way, species composition in a community is simplified to a few groups or guilds of species sharing similar traits from which we can make some predictions about nature functioning. Importantly, theseclassifications could be based on “response” traits to environmental changes or “effect” traits on ecosystem processes, and classifications based on response traits could differ from those based on effect traits.